Modeling of an Acoustic Leaky-Wave Antenna for Spatial Localization. - Fernández-Garrido, Alejandro; Campo-Valera, María; Abdo-Sánchez, María Elena; Picó, Rubén; Asorey-Cacheda, Rafael (My University, 2024)
The use of acoustic signals to locate objects in space has evolved significantly, highlighting techniques such as SONAR. An innovative alternative are Acoustic Leaky-Wave Antennas (ALWAs), which, inspired by electromagnetic Leaky-Waves Antennas (LWAs), uses a single transducer to emit directional beams by changing the operating frequency, offering a low cost and low power consumption solution for acoustic localization applications. This paper presents a numerical model of an ALWA to determine its radiation patterns, the reflection and transmission coefficients. The results are obtained using specific boundary conditions.
Keywords: Acústica submarina; Antenas; Acústica no lineal; Acoustic leaky-waves antennas; Beam scanning; Propagation; Underwater acoustic